FRI0353 Human Lymph Node Stromal Cells Obtained from Rheumatoid Arthritis Patients as Well as from Healthy Individuals Express the Autoimmune Regulator Aire. (10th June 2014) - Van Baarsen, L.G.; Hähnlein, J.; Ramwadhdoebe, T.H.; Semmelink, H.F.; Maijer, K.I.; Choi, I.Y.; Smits, N.A.; Berger, F.H.; Maas, M.; Gerlag, D.M.; Geijtenbeek, T.B.; Tak, P.P.
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune disease with unknown etiology. Immune activation in peripheral lymphoid tissues seems to precede synovial tissue inflammation. The stromal compartment of lymph nodes is crucial for the induction and shaping of immune responses. Recent murine studies have implicated a role of lymph node stromal cells (LNSCs) in tolerance due their expression of Aire. In the thymus the autoimmune regulator Aire is the main transcription factor regulating T cell central tolerance by driving expression of tissue-restricted antigens. Objectives: To investigate the expression of Aire in human LNSCs obtained during the earliest phases of RA to assess their potential role in peripheral tolerance during autoimmunity. Methods: We included autoantibody positive individuals with arthralgia without any evidence of arthritis who were positive for IgM rheumatoid factor and/or anti-citrullinated protein antibodies (n=14; RA risk group). Furthermore, we included patients with undifferentiated arthritis (n=7), RA patients (n=13) and healthy controls (n=5). All subjects underwent ultrasound-guided inguinal lymph node biopsy. LNSCs were cultured from freshly collected lymph node needle biopsies and passages 3-6 were used for experiments. LNSCs were characterized by CD45, gp38 and CD31 expression using flowcytometry (n=17). Aire was measured on mRNA level by qPCR and on protein level by flowcytometry and immunofluorescence stainings on chamber slides under homeostatic conditions and after stimulation for 24h with TLR-3 ligand polyI:C. Results: Cultured LNSCs appeared to be a mixture of fibroblastic reticular cells (FRC: gp38+, CD31-) and double negative (DN) cells. Expression of Aire could be detected at both mRNA and protein level. Aire protein expression did not correlate to gp38 expression and remained stable between homeostatic and inflammatory conditions. Immunofluorescence staining showed expected nuclear localization of Aire and was detected in the majority of cultured cells. Overall, Aire expression was highly variable between donors. Conclusions: This is the first study showing that cultured human LNSCs express Aire and our data suggest that human FRCs as well as DN cells express it. This may indicate tissue-specific self-antigen expression by human LNSCs pointing towards an important role for the lymph node stromal environment in peripheral tolerance and autoimmunity. Further functional studies will determine the possible contribution of Aire expression by LNSC in the development of RA. Acknowledgements: IMI BTCure n° 115142, EURO-TEAM n° 305549, Dutch Arthritis Foundation grant 11-1-308, Netherlands Organisation for Health Research and Development (ZonMw) Veni project 916.12.109 Disclosure of Interest: L. Van Baarsen: None declared, J. Hähnlein: None declared, T. Ramwadhdoebe: None declared, H. Semmelink: None declared, K. Maijer: None declared, I. Choi: None declared, N. Smits: None declared, F. Berger: None declared, M. Maas: None declared, D. Gerlag Employee of: GSK, Clinical Unit Cambridge, R&D Projects Clinical Platforms & Sciences, Cambridge, UK, T. Geijtenbeek: None declared, P. Tak Employee of: University of Cambridge, Cambridge and GlaxoSmithKline, Stevenage, U.K DOI: 10.1136/annrheumdis-2014-eular.5396